2016
DOI: 10.21082/ijas.v8n2.2007.p53-59
|View full text |Cite
|
Sign up to set email alerts
|

The Inheritance of Yield and Yield Components of Five Wheat Hybrid Populations Under Drought Conditions

Abstract: The magnitude of genetic inheritance and expected genetic advance are important for the prediction of response to selection in diverse environments and provide the basis for planning and evaluating breeding programs. This work investigated the inheritance of traits related to drought in wheat under natural drought conditions. Cross combinations were made to produce F 1 and F 2 hybrid populations, which were evaluated in a randomized completed block design with three replications at University of Agriculture, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 24 publications
9
28
0
1
Order By: Relevance
“…Using 20% selection intensity, the expected genetic advance for spike length was 0.48 (Table 2). The present findings are in close conformity with the research work of Ahmad et al, (2007) who also observed low magnitude of heritability for spike length. On the other hand, Memon et al, (2007), Ullah et al, (2007), Laghari et al, (2010), Eid (2009), andAjmal et al, (2009), reported high heritability for spike length.…”
Section: Results and Discussion Spike Length (Cm)supporting
confidence: 93%
See 2 more Smart Citations
“…Using 20% selection intensity, the expected genetic advance for spike length was 0.48 (Table 2). The present findings are in close conformity with the research work of Ahmad et al, (2007) who also observed low magnitude of heritability for spike length. On the other hand, Memon et al, (2007), Ullah et al, (2007), Laghari et al, (2010), Eid (2009), andAjmal et al, (2009), reported high heritability for spike length.…”
Section: Results and Discussion Spike Length (Cm)supporting
confidence: 93%
“…Mean 1000 grain weight data for the 24 wheat genotypes ranged from 32.8 g for Ghaznavi-98 x AUP-4006 to 47.3 g for Ghaznavi-98 x Pirsabak-05 with the mean value of 41.1 g (Table 3). Our findings are in close agreement with those of Ahmad et al, (2007), and Tahir et al, (2009), who also reported significant variation for 1000-grain weight among wheat genotypes.…”
Section: Grain Weight (G)supporting
confidence: 93%
See 1 more Smart Citation
“…Determining variability in yield and yield components of different cucumber genotypes will enable a breeder to know to what extent the environment affects yield (Ahmed and Khaliq, 2007;Ullah et al, 2012). Direct selection only for higher yield could be misleading because many factors interact to determine crop yield (Gatti et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly Awaad (1996) reported high heritability for grain yield and 1000 grain weight. High genetic parameters for yield associated traits such as for plant height, tillers per plant, grains per plant, 1000-grain weight by Ahmed et al (2007). High heritability coupled with high genetic advance for plant height, peduncle length, days to heading and grain yield was reported by Ijaz et al (2013).…”
Section: Introductionmentioning
confidence: 85%